Gagasan Menuju Pluralisme Agama - Cornelius Iman Sukmana (Jurnal Orientasi Baru, 2008)
We live together with others-people who have different religions. There are many religion believed by people around us. Thus, there are some ways that we can do together with others and people who have other religions. The important thing to make a good relationship to one another is the consciusness which shows that reality is plural. The attitude that I choose here is relious pluralism which is a realistic attitude that comes from that consciusness. Religious pluralism is the way that I stiil stand on my identity (my religion), and I open to others (other religions) as partners in my life. Religious pluralism, here, is defined as a way of life with others to live together, to work together, and to make our life better as a member of society.